2013
DOI: 10.1259/bjr.20120042
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle evaluation by MRI in a rabbit model of acute ischaemia

et al.

Abstract: Objective: To assess rhabdomyolysisassociated skeletal muscle changes induced by complete ischaemia in rabbits using MRI.Methods: Acute ischaemia was induced in the right hind limb of 34 New Zealand white rabbits by arterial ligation. MRI of vastus lateralis was carried out pre-operatively and every hour post-operatively up to 7 h. T 1 weighted images, T 2 weighted images with fat suppression, T 2 maps and diffusion tensor scans were obtained. The correlation of MRI findings with histopathological changes in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…These different phases could not be identified based on T 2 alone, indicating that DTI provides supplementary valuable information on muscle injury and regeneration. Similar results were shown in a study by Zhang et al 114 in ischemic muscles of rabbits, which showed an increase of MD and T 2 next to a decrease of FA values after ischemia. During histology the muscle fibers were shown to be swollen, which was accompanied by an increase of extracellular fluid.…”
Section: Ischemia and Denervationsupporting
confidence: 91%
See 1 more Smart Citation
“…These different phases could not be identified based on T 2 alone, indicating that DTI provides supplementary valuable information on muscle injury and regeneration. Similar results were shown in a study by Zhang et al 114 in ischemic muscles of rabbits, which showed an increase of MD and T 2 next to a decrease of FA values after ischemia. During histology the muscle fibers were shown to be swollen, which was accompanied by an increase of extracellular fluid.…”
Section: Ischemia and Denervationsupporting
confidence: 91%
“…90 Similar results were found in the study of femoral artery ligation. However, after 10 days in that setting diffusion values were lower than the initial " (89) " (89,90,114) 5 (89) " (89,90,114) 5 (89) Stimulated # (90) " (90) " (90) Denervation of muscles # (115,116) " (116,117,118) " (115,116) # (116,117,118) " (116) " (116) Acute: Cell swelling and increased extracellular fluid due to inflammatory response Chronic: Reduced fiber diameters due to atrophy Trauma Acute: Cell swelling and increased extracellular fluid due to inflammatory response Chemical induced # (2,88,91) " (88) " (2,88,91) # (88) " (2,88,91) " (88) Chronic: Reduced fiber diameters due to atrophy Overuse 5 (120) " (123,124) 5 (120) 5 (120) Overuse in dystrophic muscles " (120) " (120) " (120) Inflammation in polymyosit...…”
Section: Ischemia and Denervationmentioning
confidence: 80%
“…This decay reflects intramuscular water content and its organization. Although it is possible to observe four exponential nature of this decay in the normal muscle using specialized techniques, global T2 changes determined from the mono‐exponential fitting of the MR signal acquired using standard multiecho sequences are usually reported …”
Section: Discussionmentioning
confidence: 99%
“…The parameters obtained from relaxation and diffusion imaging of ischaemic hindlimbs were found to change dynamically during degeneration and regeneration processes after femoral artery ligation [18][19][20][21] and provided a useful insight into the therapeutic effects of human and mouse endothelial progenitor cells in mouse models of hindlimb ischaemia. 22,23 Recently, our group has reported that M2 macrophages are involved in the repair process of ischaemic muscle tissue after transplantation of hADSC in immunocompetent mice.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Holl et al showed an increasing of ADC values of skeletal muscles after denervation [ 30 ]. In addition, muscle ischemia increased intramuscular ADC [ 31 ]. ADC is also able to reflect fine physiological changes of skeletal muscles.…”
Section: Discussionmentioning
confidence: 99%